Fourth Five Year Plan (1969-74) Policy and Programme Government of Mysore - Planning Commission (Planning Commission, 1969)
The National Fourth Five Year Plan has described in the following terms the tasks of economic Planning in India: — “........................to organise the efficient exploitation of the resources of the country, increase production and step up the tempo of economic activity in general and industrial development in particular, to the maximum possible extent. The basic goal is a rapid increase in the standard of living of the people, through measures which also promote equality and social justice. Emphasis is placed on the common man, the weaker sections, and the less privileged/’1 There is, in this statement of unexceptionable goals, a change in emphasis from the objectives set out in the Second and Third Five Year Plans.
Government of Mysore, Planning Department